Nilai Eco-Theology Serat Kalatidha Karya Raden Ngabehi Ranggawarsita - Wahyudi, Dedi; Rijal, Syamsul; Silahuddin, Silahuddin (Tapis: Jurnal Penelitian Ilmiah, 2023)
This paper examines the eco-theologycal value of Serat Kalatidha by Raden Ngabehi Ranggawarsita. The ancient Javanese manuscript Serat Kalatidha is studied with a philosophical approach. The purpose of this study is to reveal the eco-theologycal value contained in Serat Kalatidha. This study adopted a library qualitative research methodology. The primary data source used was Serat Kalatidha by Ranggawarsita and secondary data sources were journal manuscripts, research results related to this paper. The data that has been collected is processed using philology, then the next step is data analysis with descriptive analytic. Fiber Kalatidha, reminds that humans will always be responsible for their environment so that they are in harmony with the purposes of the caliph on earth and God's creatures.